Molecular mechanism of reproductive toxicity induced by Tripterygium Wilfordii based on network pharmacology. Issue 27 (9th July 2021) - Ding, Qing; Wu, Yuanhao; Liu, Wei
Abstract : Abstract: To explore the possible molecular mechanism of reproductive toxicity of Tripterygium wilfordii from the perspective of network pharmacology and bioinformatics. The compounds of T wilfordii were obtained by querying the relevant Chinese medicine database, the effective compounds were screened and the corresponding targets were obtained, and then compared with the reproductive toxicities related to disease targets obtained from the disease gene database to infer the potential toxic targets of reproductive toxicity of T wilfordii . Then, the key targets of reproductive toxicity of T wilfordii were screened using Search Tool for the Retrieval of Interacting Genes/Protein and Cytoscape. The gene ontology function and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis, as well as module analysis, were performed on the key targets using Database for Annotation, Visualization, and Integrated Discovery and Cytoscape, respectively. Finally, the network between effective compounds-toxic targets was conducted to see how the compounds interacted. A total of 48 effective compounds and 482 potential toxic targets related to the reproductive toxicity of T wilfordii were screened. The enrichment analysis results showed that the key targets were mainly enriched in biological processes such as response to drug, ionotropic glutamate receptor signaling pathway, and KEGG pathways such as neuroactive ligand-receptor interaction, cAMP signaling pathway. In the protein-protein interaction network of potential toxic targets, there were 78 key targets such as TP53, INS, IL6, AGT, ADCY3, and so on. Enrichment analysis of the top module with 19 genes from module analysis indicated that T wilfordii might cause reproductive toxicity by gene ontology terms and KEGG pathways such as regulation of vasoconstriction, G-protein coupled receptor signaling pathway, inflammatory response, cAMP signaling pathway, and so on. In the network between effective compounds of T wilfordii and key targets, there were 5 compounds with high degree including Tingenone, Wilfordic Acid, Abruslactone A, Nobilin, and Wilforlide B. The complex molecular mechanism of reproductive toxicity of T wilfordii can be preliminarily elucidated with the help of the network pharmacology method, and the analysis results can provide some reference for the further mechanism research of reproductive toxicity of T wilfordii .